Current status, future prediction and offset potential of fossil fuel CO2 emissions in China - Cao, Jiaxi; Zhang, Jian; Chen, Ye; Fan, Rong; Xu, Lei; Wu, Entao; Xue, Yuan; Yang, Junliu; Chen, Yiming; Yang, Bo; Wu, Shuhong (Journal of cleaner production, 2023)
Reducing carbon emissions and increasing carbon sinks are key strategies to effectively remove greenhouse gases from the atmosphere. Assessing the current carbon emission status and predicting future carbon emission scenarios could help formulate effective regional carbon emission reduction targets. However, it is necessary to enhance the carbon sink capacity of terrestrial ecosystems and improve forest management methods to promote greenhouse gas absorption. In this study, the spatiotemporal characteristics and dynamic evolution of fossil fuel CO2 (FFCO2) emissions in China from 2000 to 2019 were analyzed using the standard deviation ellipse, kernel density of emissions, and Theil index. A backpropagation (BP) neural network optimized with a genetic algorithm (GA) was used to predict FFCO2 emission during 2020–2030. The biomass increment methodology was used to predict the potential carbon sinks generated by Chinese Certified Emission Reduction (CCER) carbon-sink forestry projects during 2020–2030. The results showed that China's FFCO2 emissions exhibited a gradual increasing trend during 2000–2019, with an average annual growth rate of 6.29%. China's FFCO2 emissions show a greater distribution on the southeastern coast than in the northwestern interior. The GA-BP prediction shows that China's FFCO2 emissions will continue to fluctuate and increase between 2020 and 2030. The potential of carbon sinks will be 0.69 × 108 Mg C generated by the CCER carbon-sink forestry projects during 2020–2030, which could offset 0.56% of FFCO2 emissions. In the future, imbalances in regional development should be considered when formulating carbon-reduction strategies. Moreover, using carbon-sink of forestry projects of CCER to balance economic development including poverty eradication and environmental conservation should be considered. Specifically, establishing a methodology of projects for the management of natural forests' carbon-sink will be an important future strategy. •China's FFCO2 emissions rose in volatility with an average growth rate of 6.29%.•The spatial differences of FFCO2 emissions are gradually narrowing.•FFCO2 emissions will continue to rise in the future.•Carbon-sink forestry project is ideal approach to offset carbon emission.•The Methodology of Forests Management for natural forest should be focused.